Rancang Bangun Aplikasi Ticketing Service Desk Teknologi Informasi Berbasis Website - Hidayat, Ruswan; Anwar, Nizirwan (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
Service Desk is a single point of contact (SPOC) between IT (Information Technology) serviceusers and IT service providers. Service Desks are the main entry point for users to get informationtechnology-related assistance. They act as intermediaries between users and other IT teams,ensuring that problems are resolved efficiently and effectively. This research aims to design andbuild a ticketing application for the service desk unit, by applying service level agreement to theapplication. The application built is expected to be a means of supporting activities at the servicedesk as well as being able to provide certainty for service users regarding the time required untilthe problem report is followed up.